2002
DOI: 10.1210/me.2002-0270
|View full text |Cite
|
Sign up to set email alerts
|

A Genomic Approach to Identify Novel Progesterone Receptor Regulated Pathways in the Uterus during Implantation

Abstract: The cellular actions of steroid hormone progesterone (P) are mediated via its nuclear receptors, which regulate the expression of specific target genes. The identity of gene networks that are regulated by the P receptors (PRs) in the uterus at various stages of the reproductive cycle and pregnancy, however, remain largely unknown. In this study, we have used oligonucleotide microarrays to identify mRNAs whose expression in the pregnant mouse uterus is modulated by RU486, a well-characterized PR antagonist, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 43 publications
3
128
0
2
Order By: Relevance
“…Thus, there have been several studies that have profiled gene expression patterns in the uterus after sex steroid hormone treatment of ovariectomized mice or of endometrial samples isolated at different stages of the menstrual cycle in humans (24)(25)(26)(27). In general these studies have taken RNA extracted from whole uterine tissue to profile.…”
Section: Complex Loading Onto the Chromatin Is Induced By E2 Andmentioning
confidence: 99%
“…Thus, there have been several studies that have profiled gene expression patterns in the uterus after sex steroid hormone treatment of ovariectomized mice or of endometrial samples isolated at different stages of the menstrual cycle in humans (24)(25)(26)(27). In general these studies have taken RNA extracted from whole uterine tissue to profile.…”
Section: Complex Loading Onto the Chromatin Is Induced By E2 Andmentioning
confidence: 99%
“…In order to identify progesterone-regulated pathways in the uterus during implantation, mice were treated at day 3 of pregnancy with either RU486 (a progesterone receptor antagonist) or a vehicle (Cheon et al, 2002). Tissues were collected on day 4 of pregnancy and conducted to microarray analysis to determine the difference in gene expression.…”
Section: Maternal Recognition Of Pregnancy and The Pivotal Role Of Ifmentioning
confidence: 99%
“…Several investigators reported the genes regulated by progesterone in the uterus with cDNA microarray [8,9]. Recently, gene targeting was used to create knockout mice for PR (PR knockout mouse: PRKO mouse) [10,11].…”
mentioning
confidence: 99%